2014
DOI: 10.1136/bmjopen-2014-006291
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of the morbidity associated with operative vaginal deliveries performed by day and at night

Abstract: ObjectiveTo evaluate maternal and neonatal outcomes associated with operative vaginal deliveries (OVDs) performed by day and at night.DesignProspective cohort study.SettingUrban maternity unit in Ireland with off-site consultant staff at night.PopulationAll nulliparous women requiring an OVD with a term singleton fetus in a cephalic presentation from February to November 2013.MethodsDelivery outcomes were compared for women who delivered by day (08:00–19:59) or at night (20:00–07:59).Main outcome measuresThe m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
(21 reference statements)
2
21
2
Order By: Relevance
“…In contrast to reports that found no impact of the level of experience, 4,[38][39][40][41] or to de Graaf et al, 2 who found an inverse correlation of staff seniority and neonatal adverse events, we found more adverse outcomes with increasing seniority of the attending obstetricians in the initial modelling data. More senior staff attending and increased adverse neonatal outcome seems contradictory, when assuming an association of a high level of seniority and education with good obstetric outcome; however, there might be several explanations for the present findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to reports that found no impact of the level of experience, 4,[38][39][40][41] or to de Graaf et al, 2 who found an inverse correlation of staff seniority and neonatal adverse events, we found more adverse outcomes with increasing seniority of the attending obstetricians in the initial modelling data. More senior staff attending and increased adverse neonatal outcome seems contradictory, when assuming an association of a high level of seniority and education with good obstetric outcome; however, there might be several explanations for the present findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to reports that found no impact of the level of experience, or to de Graaf et al, who found an inverse correlation of staff seniority and neonatal adverse events, we found more adverse outcomes with increasing seniority of the attending obstetricians in the initial modelling data. More senior staff attending and increased adverse neonatal outcome seems contradictory, when assuming an association of a high level of seniority and education with good obstetric outcome; however, there might be several explanations for the present findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies associated intrapartum fetal death [13], and admission to neonatal intensive care unit (NICU) [9], with births occurring during weekends. Conversely, other authors did not find any difference in the risk of poor perinatal outcome during off-hours [16–18]. This evidence of high risk of adverse outcomes during off-hours has led to a general questioning of the quality of care and availability of access to skilled care providers, organization of work and availability of equipment, and supplies during off-hours.…”
Section: Introductionmentioning
confidence: 97%